(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2016)
In this article conceptual principles of capitalization of enterprises are considered from positions foreign and Ukrainian authors and two basic going is distinguished near interpretation of essence of economic category «capitalization». Capitalization of enterprises is examined after two approaches: first – accents attention on the use of part of additional cost for the increase of capital powers of managing subjects, second – on the process of creation of fictitious capital. In the article present definitions are delimited between the marked approaches. On results an analysis authorial vision of definition is given «capitalization» as to the complex of the actions related to the increase of volume of capital of corporation and improvement of quality of his forming and use for maximization of income. On the basis of the conducted analysis quality descriptions of individual, that will provide the increase of profit of enterprise, are certain